Pengaruh Dimensi Kualitas Pelayanan Tour Leader Terhadap Loyalitas Konsumen di PT Pesona Ijen Tour and Travel Banyuwangi - Astarina P, Rika Yulia; Yustita, Aprilia Divi; Mukti, Masetya (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2021)
This research took place at PT Pesona Ijen Tour and Travel Banyuwangi, this study aims to determine the effect of quality indicators of tour leader services on consumer loyalty at PT Pesona Ijen Tour & Travel Banyuwangi and the managerial implications that can be applied at Pesona Ijen. This research is a quantitative research with survey method. The samples used in this study were customers who had used tour services from Pesona Ijen and had been accompanied by tour leader Pesona Ijen during their trip. The sampling technique uses Simple Random Sampling with a total sample of 100 peoples. Data collection techniques used interview methods, questionnaires, literature studies and documentation. The results of this study indicate that the five dimensions of service quality have a significant effect on customer loyalty at PT Pesona Ijen Tour and Travel Banyuwangi, both through partial and simultaneous testing. The influence given by the quality of tour leader services to customer loyalty at PT Pesona Ijen Tour and Travel Banyuwangi is 43% obtained through testing the coefficient of determination, whereas 57% is influenced by other variables that’s not observed in this research. Keywords: Customer Loyalty; Service Quality; Tour Leader